If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x(5x + -4) = 0 Reorder the terms: 5x(-4 + 5x) = 0 (-4 * 5x + 5x * 5x) = 0 (-20x + 25x2) = 0 Solving -20x + 25x2 = 0 Solving for variable 'x'. Factor out the Greatest Common Factor (GCF), '5x'. 5x(-4 + 5x) = 0 Ignore the factor 5.Subproblem 1
Set the factor 'x' equal to zero and attempt to solve: Simplifying x = 0 Solving x = 0 Move all terms containing x to the left, all other terms to the right. Simplifying x = 0Subproblem 2
Set the factor '(-4 + 5x)' equal to zero and attempt to solve: Simplifying -4 + 5x = 0 Solving -4 + 5x = 0 Move all terms containing x to the left, all other terms to the right. Add '4' to each side of the equation. -4 + 4 + 5x = 0 + 4 Combine like terms: -4 + 4 = 0 0 + 5x = 0 + 4 5x = 0 + 4 Combine like terms: 0 + 4 = 4 5x = 4 Divide each side by '5'. x = 0.8 Simplifying x = 0.8Solution
x = {0, 0.8}
| -4a+4(3a+3)=-8-2a | | 2y=6(-2)-10 | | p+1.6-0.4=-12 | | 2x+5y+2z=10.50 | | -5x^4+20x^2=0 | | 4x=-3x-7 | | 7y+6=180 | | 15=1.25h | | 8+8x+2x=2x+16 | | f(x-1)=x^2-14x+54 | | (2x+3.75)x-0.5=11.5 | | 3*8+2*-2= | | 6(3n-5)=(7n+6)+3 | | 9m^2+2m=10 | | 12+b=10 | | -54=a-49 | | 72=-6m | | Log(t-3)=(17-4t) | | (3x-18)(8x+32)=0 | | .5x^4-.5=0 | | -6p=58 | | -36g+40g+19g+-47g+18g=42 | | 3(8)+2(-2)= | | 1x+3y=78 | | -29=5u+6 | | 5x+7(-x+4)=14 | | 300=15w | | 25-x=280 | | =3+(-3) | | 10x-8=6x+12 | | 4x+5.8=9x+1.8 | | 7/6z+1/3=-5/6 |